Carbon Dynamics on the Molybdenum Carbide Surface during Catalytic Propane Dehydrogenation. Issue 50 (18th November 2013) - Frank, Benjamin; Cotter, Thomas P.; Schuster, Manfred E.; Schlögl, Robert; Trunschke, Annette
Abstract The effect of the gas‐phase chemical potential on surface chemistry and reactivity of molybdenum carbide has been investigated in catalytic reactions of propane in oxidizing and reducing reactant mixtures by adding H2, O2, H2O, and CO2 to a C3H8/N2 feed. The balance between surface oxidation state, phase stability, carbon deposition, and the complex reaction network involving dehydrogenation reactions, hydrogenolysis, metathesis, water‐gas shift reaction, hydrogenation, and steam reforming is discussed. Raman spectroscopy and a surface‐sensitive study by means of in situ X‐ray photoelectron spectroscopy evidence that the dynamic formation of surface carbon species under a reducing atmosphere strongly shifts the product spectrum to the C3‐alkene at the expense of hydrogenolysis products. A similar response of selectivity, which is accompanied by a boost of activity, is observed by tuning the oxidation state of Mo in the presence of mild oxidants, such as H2O and CO2, in the feed as well as by V doping. The results obtained allow us to draw a picture of the active catalyst surface and to propose a structure–activity correlation as a map for catalyst optimization.